A Topological Approach to Consumer Theory - Ferreira, M. A. M. (EasyChair Preprint Nº 7937, 2025)
The presentation of an interesting application of mathematics in economics, more concretely of topological notions in economics: the formulation of the theory of consumer basic problem built on topology, is the main target of this work. This is made grounded on the concept of preferences relation and operationalized with optimization tools.